Humanin attenuates metabolic, toxic, and traumatic neuropathic pain in mice by protecting against oxidative stress and increasing inflammatory cytokine - Bilgin, Batuhan; Hekim, Munevver Gizem; Bulut, Ferah; Kelestemur, Muhammed Mirac; Adam, Muhammed; Ozcan, Sibel; Ozcan, Mete (Pergamon-Elsevier Science Ltd, 2025)
Neuropathic pain is associated with diverse etiologies, including sciatica, diabetes, and the use of chemotherapeutic agents. Despite the varied origins, mitochondrial dysfunction, oxidative stress, and inflammatory cytokines are recognized as key contributing factors in both the initiation and maintenance of neuropathic pain. The effects of the mitochondrial-derived peptide humanin on neuropathic pain, however, remain unclear, despite its demonstrated influence on these mechanisms in numerous disease models. This study aimed to evaluate the effects of humanin on pain behavior in murine models of metabolic (streptozotocin/STZ), toxic (oxaliplatin/OXA), traumatic (sciatic nerve cuffing/cuff), and neuropathic pain. A secondary objective was to assess whether humanin modulates oxidative damage and inflammatory cytokine levels in these neuropathic pain models. Humanin (4 mg/kg) was administered intraperitoneally (i.p.) to BALB/c male mice with induced neuropathic pain over a period of 15 days, with pain thresholds assessed using hot plate, cold plate, and Von Frey tests. Serum levels of antioxidant enzymes, oxidative stress markers, and inflammatory/anti-inflammatory cytokines were measured via enzyme-linked immunosorbent assay (ELISA). In neuropathic pain-induced mice, humanin administration resulted in a statistically significant increase in pain threshold values in the STZ + Humanin, OXA + Humanin, and cuff + Humanin groups compared to their respective control groups (P < 0.05) over 15 days. Furthermore, humanin treatment significantly elevated antioxidant enzyme levels and anti-inflammatory cytokine concentrations, while reducing oxidative stress markers and pro-inflammatory cytokine levels compared to control groups (P < 0.01). These findings suggest that humanin exhibits therapeutic potential in the treatment of neuropathic pain induced by STZ, OXA, and cuff models. The ability of humanin to mitigate neuropathic pain through the suppression of oxidative stress and inflammatory cytokines indicates its promise as a novel therapeutic strategy.
Keywords: Humanin; Neuropathic pain; Reactive oxygen species; Inflammatory cytokines